2021
DOI: 10.1080/10447318.2020.1860545
|View full text |Cite
|
Sign up to set email alerts
|

Warning Apps for Road Safety: A Technological and Economical Perspective for Autonomous Driving – The Warning Task in the Transition from Human Driver to Automated Driving

Abstract: In the last decade, mobile warning apps and security services for drivers were developed, driven by the evolving market for smartphone-based applications. Now, in times of emerging autonomous vehicles, the value of warning detection in form of warning apps for road transport needs to be reappraised. In our study, we address the following questions: Does this kind of application have a technological and economical perspective for future mobility? How will the interaction between drivers, information systems (sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, some applications identified in this study also notified drivers of road conditions such as road works and hazards on the road. It has been suggested that applications that notify drivers of hazards can be beneficial for road safety (Trager et al, 2021). In addition, previous studies have indicated that applications that provide feedback for road behaviors have improved fuel consumption, decreased the probability of future phone use while driving, and can alert drivers of fatigue (Bergasa et al, 2014;Dahlinger et al, 2018;Ziakopoulos et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some applications identified in this study also notified drivers of road conditions such as road works and hazards on the road. It has been suggested that applications that notify drivers of hazards can be beneficial for road safety (Trager et al, 2021). In addition, previous studies have indicated that applications that provide feedback for road behaviors have improved fuel consumption, decreased the probability of future phone use while driving, and can alert drivers of fatigue (Bergasa et al, 2014;Dahlinger et al, 2018;Ziakopoulos et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Road safety is a top priority for the Nordic countries, and this is reflected in the implementation of road alert applications in all government institutions. These applications enable an automated transition for drivers (Trager et al, 2021). Thanks to these measures, an impressive 90% reduction in traffic incidents has been achieved, consolidating these nations as leaders in terms of the lowest rate of traffic fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, connected and autonomous vehicles (CAVs) have become a hot research topic in both academia and in the industry [1][2][3][4]. For CAVs, environmental perception is a fundamental requirement.…”
Section: Introductionmentioning
confidence: 99%